Pemberhentian Penyelidikan Penyebaran Video Porno Oleh Direktorat Reserse Kriminal Khusus (Diskrimsus) Polda Maluku - Rolan Fendri Lakoruhut; Reimon Supusepa; Erwin Ubwarin (Faculty of Law Universitas Pattimura, 2023)
ABSTRACT: The juridical study of dismissing investigations into the distribution of pornographic videos is the basis for investigators, in order to uncover a criminal act regulated in Law Number 44 of 2008 concerning pornography. The problems that can be raised are whether the case of spreading the Ambon selegram porn video is a crime and what are the juridical reasons for stopping the investigation by the Maluku Regional Police special criminal investigation directorate into the case of the Ambon selegram porn video distribution. The purpose of the research is to examine and the actions taken by vws and JP can be qualified as criminal acts of spreading pornography or not and to study and analyze juridical reasons by the directorate of special criminal investigation (Dirkrimsus) of the Maluku Regional Police. The type of research used is normative juridical. The approach used in this research is based on legislation, case approach and conceptual approach. The results of the study explain that pornographic acts are unlawful and for this reason, perpetrators can be held accountable for the law. In this context, criminal law is one of the means that is expected to be able to deal with pornographic crimes against vws and jp.